Colorado Agricultural Workers' Rights of Access to Key Healthcare Providers: A Policy Brief - Stallones, Lorann; Valley, Morgan; Pennington, Whitney (Frontiers in Public Health, 2022)
Health is a human right. In order to exercise their right to health, agricultural workers need to have access to medical, dental, and behavioral health care. Agricultural workers need to have medical, dental, and behavioral health care available at times and locations that are amenable to their work schedules and worksites. Many agricultural workers do not have access to transportation due to the nature of their working conditions, therefore policies to provide transportation will increase access to medical, dental, and behavioral health services.